ANALYSIS OF WORK ENVIRONMENT, WORK DISCIPLINE AND COMPETENCIES ON EMPLOYEE PERFORMANCE AT PT. PERKEBUNAN NUSANTARA IV REGIONAL I MEDAN - Anjani Intan; Ikhah Malikhah; Muhammad Toyib Daulay (RADJA PUBLIKA, 2024)
The research analysis aims to find out whetherwork environment, work discipline and competence influence employee performance. The data analysis technique used is an associative research method with the help of the SPSS version 19 program. This research uses multiple linear regression analysis. The sample in this study was 55 respondents. Primary data collection uses a questionnaire. The research results show that lWork environment has a partially positive and significant effect on employee performancePT Perkebunan Nusantara IV Regional I Medan. Work discipline has a partially positive and significant effect on employee performancePT Perkebunan Nusantara IV Regional I Medan. Competence has a partially positive and significant effect on employee performancePT Perkebunan Nusantara IV Regional I Medan. The work environment, work discipline and competence simultaneously have a positive and significant effect on employee performancePT Perkebunan Nusantara IV Regional I Medan.